Body scrub containing virgin coconut oil, coffee grounds (Coffea arabica Linn) and carbon active coconut shell (activated carbon Cocos nucifera L) as a moisturiser and a skin brightener - Putri, Desi Eka; Djamil, Ratna; Faizatun, Faizatun (Scripta Medica, 2021)
Introduction: Virgin Coconut Oil (VCO) contains a lot of medium chain fatty acids. VCO combined with coffee grounds (Coffea arabica Linn) and activated carbon (Activated carbon Cocos nucifera L) has the potential to form a preparation that can moisturise and brighten the skin. The purpose of this study was to make cosmetic cleansing preparations containing three natural ingredients.Methods: This study evaluated the organoleptic body scrub preparations, homogeneity, dispensability and pH for three different formulations. In vivo test for irritation (oedema and erythema) was carried out on albino rabbits (n = 3) for each treatment group. Clinical irritation testing was performed on the forearm of healthy volunteers, 17 - 45 years of age with no history of allergies (n = 30). Determination of skin moisture content and melanin index was carried out as a measure of effectiveness.Results: Organoleptic and homogeneity tests showed that preparations had dark black colour, the distinctive smell of coffee, it was homogeneous, spread ability was in the range of 4 cm with the pH at a safe pH for the skin. Irritation results also did not show any oedema and erythema in in vivo testing. In clinical testing no irritation occurred by testing the body scrub samples. Body scrubs routinely used by volunteers for 2 months increased moisture on the skin as well as brightness (p < 0.05).Conclusion: Body scrub creams containing VCO, coffee grounds and activated carbon are preparations that have the potential to be cosmetic cleansers.
Keywords: Body scrub; Virgin coconut oil; Coffee grounds; Activated carbon